A microRNA involved in the germinal center reaction - Küppers, Ralf (American Society of Hematology, 2014)
In this issue of Blood, de Yébenes et al identify miR-217 as a promoter of the germinal center reaction, partly by suppressing the DNA damage response. Overactivity of miR-217 is hence potentially dangerous, and, indeed, its uncontrolled expression causes lymphomas.(1)